Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1680/jmacr.16.00525
|View full text |Cite
|
Sign up to set email alerts
|

Structural behaviour of reinforced concrete beams containing crumb rubber and steel fibres

Abstract: This paper presents experimental work to investigate the strength and cracking characteristics of optimised self-consolidating and vibrated rubberised concrete mixtures with/without steel fibres (SFs) using large-scale reinforced concrete beams. The test beams were cast with varying percentages of crumb rubber (CR) (0 to 35%), SF volume fractions (0, 0·35 and 1%) and SF lengths (35 and 60 mm). The performance of some design codes and published empirical equations was evaluated in predicting the shear capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…As a new type of reinforced material of concrete, steel fiber has excellent mechanical properties. Considerable studies have shown that adding steel fibers into concrete can improve the mechanical performance of concrete structural components, by delaying the development of microcracks into macrocracks, hindering the development of macrocracks and leading to stress redistribution [13][14][15][16][17][18][19][20]. Li and Li [21] studied the effects of 0.9% steel fiber volume fraction and 5% rubber particle content on the mechanical properties of high-strength concrete, including flexure, compression, and seismic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As a new type of reinforced material of concrete, steel fiber has excellent mechanical properties. Considerable studies have shown that adding steel fibers into concrete can improve the mechanical performance of concrete structural components, by delaying the development of microcracks into macrocracks, hindering the development of macrocracks and leading to stress redistribution [13][14][15][16][17][18][19][20]. Li and Li [21] studied the effects of 0.9% steel fiber volume fraction and 5% rubber particle content on the mechanical properties of high-strength concrete, including flexure, compression, and seismic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the ductility index (μ) was used to assess the influence of crumb rubber on the deformability of all the tested beams. Generally, the inclusion of the crumb rubber in beams can contribute to improving strain and deformability and enhancing the duality in terms of increase [6,29]. For instance, increasing the rubber from 0-15 % in the rubberized and hybrid rubberized concrete beams, which increased the ductility by 110.…”
Section: Figure 9 Total Energy (Toughness) Resultsmentioning
confidence: 99%
“…The crack propagation and its spacing for the rubberized and hybrid rubberized concrete of tested beams were measured. According to previous studies [6,21,29,30], when the crumb rubber was added to conventional concrete, it caused more cracks. This indicates that the spacing between the two cracks will become lower whether for maximum or minimum spacing.…”
Section: (B)mentioning
confidence: 96%
“…The particles of CR treated by different methods and materials, such as H 2 SO 4 [47], NaOH [38,80,81], Ca(OH) 2 [47], KMnO 4 [82], CH 3 COOH [47], silane coupling agent (SCA) [32], ethanol [77] limestone powder and treatment [83], methanol [77], silica fume (SF) [84], cement [84], pre-coated fibers [37,69,85,86], metakaolin (MK) [35], ground granulated blast furnace slag (GGBS) [35], sand powder (SP) [57], glass powder (GP) [57], natural zeolite [38], and nano silica (NS) [40]. However, the use of steel fibers in the CR concrete results to enhanced flexural strength and splitting tensile strength, but it did not improve the compressive strength and modulus of elasticity properties [87,88].…”
Section: Hardened Properties Of Cr Concretementioning
confidence: 99%